FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PRE MENSTRUAL SYNDROME PADA MAHASISWA TK II SEMESTER III JURUSAN KEBIDANAN POLTEKKES KEMENKES MATARAM - Syajaratuddur Faiqah; Rita Sopiatun (poltekkes kemenkes mataram, 2015)
Abstract: Premenstrual syndrome is a physical and psychological symptoms that occurs at 7 to 10 days before menstruation and disappear during menstruation. Premenstrual Syndrom ( PMS ) is a combination of symptoms that occur before menstruation and disappear with the release of menstrual blood, as well as experienced by many women before or during each menstrual cycle. The high PMS problems in adolescents will have an impact on productivity in performing daily activities. Objective of this research is to To Know Factors Associated With Premenstrual Syndrome. This is a cross section of survey methods research design. The samples in this study were 70 students of the Midwifery, sampling technique is the Purposive sampling, the data collected by distributing questionnairs. The results of the chi-square test, there is significant relationship between stress and Premenstrual Syndrom / PMS (p=0,036). And there is no significant relationship between Consumption Patterns, Activity/sport Pattern and Premenstrual Syndrom ( p=0,627).